The fishes of Tristan Da Cunha and Gough Island (South Atlantic), and the effects of environmental seasonality on the biology of selected species - Andrew, Timothy Gilbert (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1993)
This study focuses on the taxonomy, biogeography and biological aspects of the fishes of Tristan da Cunha and Gough Island in the cental South Atlantic Ocean. Oceanographic measurements were undertaken to determine the position and nature of the Subtropical Convergence (STC) in the vicinity of the islands. The Tristan da Cunha group is thought to be situated on the northern edge of the STC while Gough Island is situated on the southern edge of the front. The seasonal environmental cycle at the islands is characterised by an annual sea surface temperature fluctuation of approximately 5 Â°C and an annual change in stratification of the water column. It is suggested that this increase in stratification at the STC, brought about in the summer by insolation warming the surface layers of the ocean, enhances primary production. The STC is identified as a unique habitat for fishes and as an important barrier to dispersal of species in the Southern Ocean. The present study has produced 18 new distributional records from the shelf waters of Tristan da Cunha and Gough Island. The fish fauna known from the shelf waters of these islands is reviewed, and a diagnosis, synonymy, and in some cases an illustration are provided. For certain species, brief notes on their biology, relative abundance and seasonal distribution are included. An analysis of the ichthyofaunal relationships between shallow water areas in the vicinity of the STC has resulted in the identification of a characteristic neritic STC ichthyofauna. The circumglobal distribution of many of these species is thought to be a consequence of a dispersive pelagic phase in their life-cycles. Biological processes in fishes at these islands are temporally and spatially affected by seasonal changes in oceanographic conditions. Seasonal sea temperature variation was identified as being an indicator of other oceanographic phenomena that may affect processes such as growth, reproduction and feeding in fishes at the islands. Most species have a summer spawning season and growth rate increased during the summer months. It was hypothesised that enhanced primary production and a related increase in food quality and availability during the summer were the major factors temporally regulating the growth and reproduction of fishes at the islands. Twenty families of neritic fishes have been recorded in the shelf waters of Tristan da Cunhaand Gough Island. Most families are represented by only one species. Because of this a wide range of life-history strategies are apparent in the fauna. Nevertheless, there are a number of common life-history characteristics shared by most of the neritic species. Firstly, the early lifehistory of many species included an extended pelagic phase which might have facilitated colonisation throughout the STC zone in the past, thereby regulating extant species diversity in this region. Secondly, the common occurrence of an extended summer breeding season and iteroparity suggested that these characters also contributed to survival in what is considered to be an unpredictable environment. It would appear that these common characteristics hold the key to the success of many fishes in the STC zone. This study has contributed to our understanding of oceanic island ecosystems and has revealed distributional patterns of fishes that were unknown previously. By focusing on the biological processes of selected species the regulatory role played by local environmental conditions became apparent. The results of this study are also relevant to proposed conservation measures for Tristan da Cunha and Gough Island.
Keywords: Fishes -- Tristan da Cunha; Fishes -- Gough Island Fishes -- Conservation